Novel Drug Delivery Technologies and Targets for Renal Disease. Issue 9 (2nd June 2022) - Chade, Alejandro R.; Bidwell, Gene L.
Abstract : The burden of acute and chronic kidney diseases to the health care system is exacerbated by the high mortality that this disease carries paired with the still limited availability of comprehensive therapies. A reason partially resides in the complexity of the kidney, with multiple potential target cell types and a complex structural environment that complicate strategies to protect and recover renal function after injury. Management of both acute and chronic renal disease, irrespective of the cause, are mainly focused on supportive treatments and renal replacement strategies when needed. Emerging preclinical evidence supports the feasibility of drug delivery technology for the kidney, and recent studies have contributed to building a robust catalog of peptides, proteins, nanoparticles, liposomes, extracellular vesicles, and other carriers that may be fused to therapeutic peptides, proteins, nucleic acids, or small molecule drugs. These fusions can display a precise renal uptake, an enhanced circulating time, and a directed intraorgan biodistribution while protecting their cargo to improve therapeutic efficacy. However, several hurdles that slow the transition towards clinical applications are still in the way, such as solubility, toxicity, and sub-optimal renal targeting. This review will discuss the feasibility and current limitations of drug delivery technologies for the treatment of renal disease, offering an update on their potential and the future directions of these promising strategies.